2022
DOI: 10.1155/2022/3850582
|View full text |Cite
|
Sign up to set email alerts
|

Network Intrusion Detection Method Based on Improved CNN in Internet of Things Environment

Abstract: In view of most existing intrusion detection technologies that cannot meet the actual needs of the Internet of Things and facing the problems of poor detection effect of complex network intrusion methods, a network intrusion detection method based on deep learning algorithm in the environment of the Internet of Things is proposed. Firstly, the Internet of Things intrusion detection model is constructed based on edge computing, in which the concept of gated convolution is introduced to improve the convolution n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 27 publications
0
0
0
Order By: Relevance
“…However, since shallow machine learning methods are susceptible to spoofing attacks and are difficult to adapt to complex network attacks, more and more researchers are utilizing the adaptive and characterization capabilities of deep learning to automatically learn effective feature representations and perform pattern recognition from high-dimensional and massive network traffic data to improve the performance of intrusion detection models. Researchers have recently applied numerous deep learning techniques in intrusion detection scenarios within the industrial internet field, such as Convolutional Neural Networks (CNN [8,9]), Temporal Convolutional Networks (TCN [10]), Generative Adversarial Networks (GAN [11,12]), Long Short-Term Memory Networks (LSTM [13,14]), and some related combinations (CNN-LSTM [15]) aiming at further capturing the feature representations of network traffic.…”
Section: Introductionmentioning
confidence: 99%
“…However, since shallow machine learning methods are susceptible to spoofing attacks and are difficult to adapt to complex network attacks, more and more researchers are utilizing the adaptive and characterization capabilities of deep learning to automatically learn effective feature representations and perform pattern recognition from high-dimensional and massive network traffic data to improve the performance of intrusion detection models. Researchers have recently applied numerous deep learning techniques in intrusion detection scenarios within the industrial internet field, such as Convolutional Neural Networks (CNN [8,9]), Temporal Convolutional Networks (TCN [10]), Generative Adversarial Networks (GAN [11,12]), Long Short-Term Memory Networks (LSTM [13,14]), and some related combinations (CNN-LSTM [15]) aiming at further capturing the feature representations of network traffic.…”
Section: Introductionmentioning
confidence: 99%
“…In the same way, we compare the performance of EFedID with some of the latest other notable state-of-the-art methods. Models CNN [37] and NIDS-CNNLSTM [38] were both trained using the KDDTrain + dataset and tested using the KDDTest + dataset. Te model SMOTE-GAN-VAE [39] was evaluated on the NSL-KDD and CICIDS 2017 datasets, respectively.…”
Section: Performance Comparison With Other Latest Methodsmentioning
confidence: 99%
“…A similar trend is observed in the KDD CUP 99 dataset, where EFedID with c � 0.7 attains the highest accuracy of 0.9735, followed by EFedID with c � 0.5 (accuracy of 0.9712) and EFedID with c � 0.3 (accuracy of 0.9706). Once again, all models with varying c values CNN [37] 92.14 Tree-stage SMOTE-GAN-VAE [39] 94.0 NIDS-CNNLSTM [38] 97.05 EFedID 97.3…”
Section: Impact Of Cmentioning
confidence: 99%
“…Moreover, they stated that IoT encounters many significant challenges in this era of vast amounts of data and information: large quantities of data redundancy, bottlenecks in cloud processing power, data security, and privacy. In the related research on intrusion detection techniques, it was found that most intrusion detection techniques fail to meet the actual demand standards of IoT, and there are also problems of poor detection of complex network intrusion methods [8].…”
Section: Introductionmentioning
confidence: 99%